2020
DOI: 10.1080/1475939x.2020.1854337
|View full text |Cite
|
Sign up to set email alerts
|

High school students’ experience of online learning during Covid-19: the influence of technology and pedagogy

Abstract: The Covid-19 pandemic resulted in New Zealand schools closing and teaching occurring through digital media. This article reports research which applied Kearney et al.'s framework as a lens to examine student experience of digital learning at home during Covid-19. This framework provides three characteristics that influence learners' experience when using digital devices for learning: personalisation, authenticity and collaboration. High school students in their final two years of schooling (n = 1975) responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
166
1
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(192 citation statements)
references
References 13 publications
9
166
1
16
Order By: Relevance
“…While students engaged with content, they did not achieve other aspects for effective online learning such as social, cognitive and teaching presence and supporting discourse. Motivation and engagement in learning was also a key theme identified through a survey of senior secondary students from New Zealand (Yates et al, 2020). The students in this study reported that authenticity and collaboration facilitated their learning, and they valued supportive pedagogies and motivational strategies which enabled their academic progress and enhanced wellbeing.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…While students engaged with content, they did not achieve other aspects for effective online learning such as social, cognitive and teaching presence and supporting discourse. Motivation and engagement in learning was also a key theme identified through a survey of senior secondary students from New Zealand (Yates et al, 2020). The students in this study reported that authenticity and collaboration facilitated their learning, and they valued supportive pedagogies and motivational strategies which enabled their academic progress and enhanced wellbeing.…”
mentioning
confidence: 75%
“…Public policies in education should be oriented towards the teachers' professional learning within the transformation of educational models rather than the provision of technological resources. In addition, in emergency situations, teachers need to be able to provide emotional support for students (Palau et al, 2021;Yates et al, 2020), and for teachers of younger children and those with special needs they need to be confident in adapting their practices to collaborate with parents (Parmigiani et al, 2020). In addition, the blurring of the home and school boundaries has implications for future digital infrastructure policies.…”
Section: Equity Planning For the Future And Valuing Teachersmentioning
confidence: 99%
“…Public policies in education should be oriented towards the teachers' professional learning within the transformation of educational models rather than the provision of technological resources. In addition, in emergency situations, teachers need to be able to provide emotional support for students (Palau et al, 2021;Yates et al, 2020), and for teachers of younger children and those with special needs they need to be confident in adapting their practices to collaborate with parents (Parmigiani et al, 2020). In addition, the blurring of the home and school boundaries has implications for future digital infrastructure policies.…”
Section: Equity Planning For the Future And Valuing Teachersmentioning
confidence: 99%
“…Di Pietro et al (2020) emphasize that the transition to remote teaching can lead to students spending far less time learning than they would in the classroom. Some students have difficulties with organizing their time and activity, which makes them feel they have more freedom because no one is supervising them (Yates et al, 2020). This lack of skills and the loss of their daily school routine diminishes students' motivation to learn and carry out their responsibilities, leading to a lesser amount of time spent on learning.…”
Section: Proceedings Of Intcess 2021 8th International Conference On Education and Education Of Social Sciences 18-19 January 2021mentioning
confidence: 99%
“…One of the most significant changes with which students were faced was the change in the means of communication with their teachers and peerscommunication was brought into the virtual world. Yates et al (2020) state that students prefer "face-to-face" communication in the classroom due to the physical closeness of their teacher and peers, as well as the direct support and feedback they receive from them. On the other side, communication through applications such as Zoom, which were not used before, seemed unnatural to students because only one person could talk at a time, most frequently the teacher.…”
Section: Proceedings Of Intcess 2021 8th International Conference On Education and Education Of Social Sciences 18-19 January 2021mentioning
confidence: 99%